Targets of statins intervention in LDL-C metabolism: Gut microbiota - Sun, ChangXin; Wang, ZePing; Hu, LanQing; Zhang, XiaoNan; Chen, JiYe; Yu, ZongLiang; Liu, LongTao; Wu, Min (Frontiers in Cardiovascular Medicine, 2022)
Increasing researches have considered gut microbiota as a new “metabolic organ,” which mediates the occurrence and development of metabolic diseases. In addition, the liver is an important organ of lipid metabolism, and abnormal lipid metabolism can cause the elevation of blood lipids. Among them, elevated low-density lipoprotein cholesterol (LDL-C) is related with ectopic lipid deposition and metabolic diseases, and statins are widely used to lower LDL-C. In recent years, the gut microbiota has been shown to mediate statins efficacy, both in animals and humans. The effect of statins on microbiota abundance has been deeply explored, and the pathways through which statins reduce the LDL-C levels by affecting the abundance of microbiota have gradually been explored. In this review, we discussed the interaction between gut microbiota and cholesterol metabolism, especially the cholesterol-lowering effect of statins mediated by gut microbiota, via AMPK-PPARγ-SREBP1C/2, FXR and PXR-related, and LPS-TLR4-Myd88 pathways, which may help to explain the individual differences in statins efficacy.